Emerging Online Tafsir Platforms and their Impact on Qur’anic Da’wah in Southeast Asia - Abdul Hamid (JURNAL ISLAM NUSANTARA, 2025)
The rapid expansion of digital media has significantly transformed religious communication, including the dissemination of Qur’anic interpretation across Southeast Asia. Online tafsir platforms have emerged as influential mediums through which Islamic teachings are articulated, interpreted, and engaged with by diverse audiences in the digital age. This study aims to examine how these platforms contribute to contemporary Qur'anic da'wah, particularly in terms of discursive construction, interpretive authority, and audience interaction, and a qualitative approach with digital discourse analysis combined with virtual ethnography. Employing a literature-based qualitative approach grounded in Critical Discourse Analysis, the research systematically reviewed 30 peer-reviewed publications focused on digital tafsir content within the Southeast Asian context. The findings reveal that online tafsir platforms not only increase accessibility to Qur’anic knowledge but also reshape the rhetorical and ideological dimensions of religious interpretation through interactive media, localized narratives, and evolving discourse strategies. These platforms increasingly mediate between traditional theological norms and contemporary sociocultural realities, often facilitating pluralistic and contextualized understandings of scripture. The study contributes theoretically by integrating Islamic studies with discourse analysis, offering a novel analytical framework to interrogate religious communication in digital environments.